2016
DOI: 10.1177/0022427816678908
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Determinants of Situated Choice in Situational Action Theory

Abstract: Objectives: This study extends theoretical arguments from situational action theory (SAT) by focusing on the enduring effects of neighborhood context on individual criminal involvement and presents the first direct multilevel assessment of SAT in non-Western contexts using neighborhood data. Methods: Survey data from a random sample of 1,435 adults in 41 neighborhoods in Russia and Ukraine are used to assess the interplay between individual criminal propensity and moral and deterrent qualities of neighborhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
3
20
0
1
Order By: Relevance
“…SOCIOINFORM: Center for Sociological Research, a Ukrainian research organization with an extensive record of conducting surveys for many international organizations including United Nations, collected the data. The survey instrument contains items validated in prior survey of adults in Ukraine conducted by SOCIOINFORM (e.g., see Antonaccio et al, 2017; Antonaccio & Tittle, 2008) as well surveys in other cross-national locations (e.g., Hobfoll et al, 2006). The questionnaire was written in English, translated into Ukrainian and Russian, and then back translated into English by linguists fluent in these languages.…”
Section: Methodsmentioning
confidence: 99%
“…SOCIOINFORM: Center for Sociological Research, a Ukrainian research organization with an extensive record of conducting surveys for many international organizations including United Nations, collected the data. The survey instrument contains items validated in prior survey of adults in Ukraine conducted by SOCIOINFORM (e.g., see Antonaccio et al, 2017; Antonaccio & Tittle, 2008) as well surveys in other cross-national locations (e.g., Hobfoll et al, 2006). The questionnaire was written in English, translated into Ukrainian and Russian, and then back translated into English by linguists fluent in these languages.…”
Section: Methodsmentioning
confidence: 99%
“…Criminology theories have proposed that people's legal and moral judgments have central roles in guiding their behavior (Antonaccio et al 2017;Wikström 2006;Wikström et al 2011). Nevertheless, neither consumers' legal judgments, nor the similarities and discrepancies between their legal and ethical judgments has been studied.…”
Section: Conclusion Discussionmentioning
confidence: 99%
“…For instance, it has been shown that financial gains and ego revenge promote dysfunctional behavior (Daunt and Harris 2012). However, criminology theories have highlighted people's legal and moral judgments as the central determinants of their behavior (Antonaccio et al 2017). Specifically, the situational action theory has proposed that people's actions depend on the way that they perceive their action alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…To test the interaction effects of crime propensity and criminogenic exposure, we followed the tradition of SAT research in operationalizing crime propensity by creating a composite scale containing both dimensions of low self-control and low morality (Antonaccio et al, 2017). Then, two products of Crime Propensity × Unsupervised Leisure Activities and Crime Propensity × Delinquent Peers were created.…”
Section: Methodsmentioning
confidence: 99%